Diseño de un relleno sanitario manual para el distrito de Parcoy - La Libertad 2016 - Morín Montoya, Arturo Hamilton (2017)
This research is to presents the design of a Manual Sanitary Landfill for an adequate final disposal of Solid Waste in the district of Parcoy - La Libertad, carrying out an analysis of the bibliographic review, satellite images, documents and a situational diagnosis of the district. The purpose is to mitigate the pollution generated by local solid waste in the district of Parcoy, through the evaluation and analysis of technical criteria, description of engineering studies and in accordance with current environmental regulations. The importance of this study is based on having a landfill as a complex and definitive method, considering its capacity to receive all types of solid waste and thus contributing to reduce pollution to the environment and human health. Various basic and technical studies were carried out in the work methodology, using different methods provided by the environmental engineering branch, which served as information and basic parameters for the satisfactory development of the project. The results shows that the total daily generation of solid waste in the district of Parcoy in year of starting (year 2018) is 8. 795 Tn / day, in addition to that segregating recyclable waste the amount of solid waste is reduced at 5.612 Tn / day; according to the daily generation of RR.SS. less than 20 Tn / day, the landfill to be designed will be a manual type with a cumulative volume capacity of 133,891.49 cubic meters, requiring an approximate area of 6.3 hectares for a useful life of 16 years, according to the needs of the district